2017
DOI: 10.1016/j.ijer.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative cognitive-activation strategies as an emancipatory force in promoting girls’ interest in and enjoyment of mathematics: A cross-national case study

Abstract: The results of international large-scale assessments have revealed the emergence of gender disparities in attitudes to mathematics, with girls generally demonstrating lower levels of interest in and enjoyment of mathematics than boys. Given that attitudes to mathematics are key determinants of future STEM participation, collaborative cognitive-activation teaching strategies, which harmonise with the core tenets of feminist mathematical pedagogy, are proposed as a possible approach to improving girls' relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
1
23
0
3
Order By: Relevance
“…It should be noted that in recent years attempts to counter stereotypical beliefs of mathematics as a male domain have been put forward with more inclusive feminist mathematics pedagogies (Cantley, Prendergast, and Schlindwein 2017;Jacobs and Becker 1997). These pedagogies fall broadly in line with the more modern social constructivist approach to mathematics education described previously.…”
Section: Gender Differences In Mathematics Achievement and Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that in recent years attempts to counter stereotypical beliefs of mathematics as a male domain have been put forward with more inclusive feminist mathematics pedagogies (Cantley, Prendergast, and Schlindwein 2017;Jacobs and Becker 1997). These pedagogies fall broadly in line with the more modern social constructivist approach to mathematics education described previously.…”
Section: Gender Differences In Mathematics Achievement and Participationmentioning
confidence: 99%
“…It has been suggested that women in particular learn better as connected knowers, with mathematics not taught as an abstract science, but related to the students' own experiences, and in a supportive atmosphere of collaborative learning (Jacobs and Becker 1997). Furthermore, it has been shown that using such collaborative strategies in classrooms today could improve girls' interest in and enjoyment of mathematics as a school subject (Cantley, Prendergast, and Schlindwein 2017). It is hoped that these viewpoints, alongside international policy change will increase the breadth and depth of equal access to mathematics education (Spielman 2008).…”
Section: Gender Differences In Mathematics Achievement and Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…STEM discoveries happen via collaboration and the communication of STEM is inherently social and community-oriented. Research provides evidence of the benefits of creating programs that include collaboration and community responsiveness as beneficial to girls' sense of belonging to STEM (Adams et al, 2014;Buck et al, 2014;Cantley et al, 2017;Riedinger and Taylor, 2016). Working with others in an inclusive, collegially nurturing space increases girls' confidence about their ability, allows them to exchange ideas and consider and explore their own and diverse perspectives (Riegle-Crumb and Morton, 2017).…”
Section: Emphasize That Stem Is Collaborative Social Andmentioning
confidence: 99%
“…whereas males have a tendency to be 'separate knowers'. In terms of mathematical problem solving, connected knowing would be deemed more open to solving problems in multiple ways and relating to personal experiences [39] and this may explain why females scored significantly higher on this construct.…”
Section: Do Students Believe That There Are Word Problems That Cannotmentioning
confidence: 99%